Bud, Not Buddy - Curtis, Christopher Paul (Random House, Inc., 1999)
It$1 (Bs 1936, in Flint Michigan. Times may be hard, and ten-year-old Bud may be a motherless boy on the run, but Bud$1 (Bs got a few things going for him: He has his own suitcase full of special things; He$1 (Bs the author of Bud Caldwell$1 (Bs Rules and Things for Having a Funner Life and Making a Better Liar Out of Yourself; His momma never told him who his father was, but she left a clue: flyers advertising Herman E. Calloway and his famous band, the Dusky Devastators of the Depression!!!!!! Bud$1 (Bs got an idea that those flyers will lead him to his father. Once he decides to hit the road to find this mystery man, nothing can stop him$1 (Bnot hunger, not fear, not vampires, not even Herman E. Calloway himself.s
Keywords: Historical; Juvenile Fiction; People and Places